Comparison of clinical and radiographic changes in peri-implant tissues in two implant connection designs - Arias , Melissa Botero; Botero , Melissa Castaño; Ríos , María Fernanda Quiroga; Patiño, Jorge Eliecer (Seven Editora, 2023)
A dental implant is known as a piece composed of a biocompatible material that is inserted into the bone to replace the root of a tooth. There are different types of designs for internal connections between the implant and the abutment. Among the most commonly used are the conical connection (CC) and the internal hex connection (HI), the choice of one of them can determine the prognosis of the procedure. That said, a cross-sectional case report study was carried out where 10 implants inserted in 3 patients were observed, and clinical parameters such as probing depth, presence of bleeding, redness and gingival exudate were analyzed. In addition, radiographs measured the distance between the bone crest and the implant platform, on the mesial and distal surfaces, to assess bone loss. DOI:https://doi.org/10.56238/sevened2023.004-001